Crescimento e produção do maracujazeiro amarelo, sob diferentes fontes e doses de fósforo em cobertura - Santos, Gaudencio Pereira dos; Lima Neto, Antonio João de [UNESP]; Cavalcante, Lourival Ferreira; Lucena Cavalcante, Italo Herbert; Luna Souto, Antonio Gustavo de (Univ Federal Uberlandia, 2014)
Brazil is the largest world producer of yellow passion fruit, a fruit crop which is exigent in nutrients, although little studied in relation to phosphorus fertilizing, fundamental on plant establishment. An experiment was carried out during the period of March/2010 to April/2011 in Remigio County, Paraiba State, Brazil, in order to evaluate the vegetative and productive attributes of yellow passion fruit plants under different sources and doses of phosphorus. Treatments were distributed in randomized blocks in tree replications and twelve plants by plot using the factorial design 2 x 5 referring the sources of superphosphate triple and superphosphate simple at levels P2O5 of 0, 12, 18, 24 and 30 g cave(-1). The following variables were recorded: stem diameter, number of productive branches, number of fruits per plant, fruit mass and fruit yield. The sources and doses of phosphorus affected growth and fruit production of yellow passion plants. The triple superphosphate is the most phosphorus efficient source for growth and fruit production of yellow passion fruit. The triple superphosphate dose which promoted the maximum yield of yellow passion fruit is 42.86 g.

O Brasil é o maior produtor mundial do maracujazeiro amarelo, uma cultura exigente em nutrientes, mas pouco estudada quanto à adubação fosfatada, fundamental no estabelecimento da cultura. Nesse sentido, um experimento foi desenvolvido no período de março de 2010 a abril de 2011, no município de Remígio, PB, objetivando avaliar os atributos vegetativo e produtivo do maracujazeiro amarelo cultivar IAC 273/277 + 275 sob adubação com diferentes fontes e doses de fósforo em cobertura. O ensaio foi instalado em blocos ao acaso, em três repetições e 12 plantas por parcela, num arranjo fatorial de 2 x 5, referente às fontes de superfosfato simples e triplo, nas doses de 0, 12, 18, 24 e 30 g de P2O5 cova-1. Foram avaliadas as seguintes variáveis: diâmetro do caule, número de ramos produtivos, número de frutos por planta, massa média de frutos, produção por planta e produtividade. As fontes e doses de fósforo influenciam o crescimento e produção do maracujazeiro amarelo. O superfosfato triplo é a fonte fosfatada mais eficiente para o crescimento e produção do maracujazeiro amarelo. A dose com a máxima produtividade de maracujazeiro amarelo é 42,86 g de superfosfato triplo.
Growth and production of yellow passion fruits plants under different sources and doses of phosphorus
Keywords: Phosphorus fertilizing; Passiflora edulis Sims; Plant fruit revenue; Adubação fosfatada; Passiflora edulis Sims; rendimento de plantas